Effects of stair-climb marathon on participants: a case study of step-up event / Muhammad Zulhelmi A. Suhaimi... [et al.] - A. Suhaimi, Muhammad Zulhelmi; M. Tohid, Umairah; Kinson, Audrey Fiona; Johari, Nasuha; A. Rahman, Fatin Zakiah; Mahdzar, Mazlina (Universiti Teknologi MARA, Negeri Sembilan, 2017)
This study examines effects of Stair-climb marathon on participants using a quantitative survey. It was found that participations have a positive effect on the marathon impact towards their health and wellness. Thus, the result indicates the higher the number of satisfaction on stair-climb marathon impact towards their body, the lower are the negative impact of marathon. These results will provide benefits for stair climb marathon on participations and enable them to formulate appropriate strategies for next marathon event. This study also seeks to contribute the positive impact of marathon toward human body health.